Impact of low pass filters of the droop control on converter-interfaced DERs of an islanded microgrid - Shahnia, Farhad (2016)
© 2016 IEEE.This paper focuses on different types of low pass filters (LPFs) that are used to calculate the average active and reactive power, when using a droop control for the operation of converter-interfaced distributed energy resources (DERs) in an islanded microgrid. Instantaneous powers have a dc value and an oscillatory part which needs to be filtered out properly before being applied to the droop controller. A comparison of different types of LPFs is presented from their time-domain step response and frequency-domain response perspectives. Later, the impact of each of the considered filters is investigated on the operation of DERs within an islanded microgrid.